The Waltz’s Third Level of Analysis and China’s Pursuit of Legitimacy Via the AIIB - Abdul Aziz, Nuruddin (WILAYAH: The International Journal of East Asian Studies, 2020)
Abstract: Since 2016, the Asian Infrastructure and Investment Bank (AIIB) has assisted countries in improving their economic conditions with infrastructure and transport projects. Publicly proposed in 2013 by China’s President, Xi Jinping, during his state visit to Indonesia, the AIIB has helped consolidate China’s legitimacy as a leading power in Asia and globally. Thus, this paper argues that forming the AIIB was a move to counter the relatively low vote share in the neoliberal’s international financial institutions, namely the World Bank, the International Monetary Fund (IMF), and the Japan-led Asian Development Bank (ADB). With the added benefit of leading a development institution, more legitimacy is gained via the international system. Since its establishment, AIIB had significantly increased from 57 founding members in 2016 to 103 in 2020. In examining how this translates into China gaining legitimacy from the international system, this paper examined the case of China’s AIIB through the Third Level of Analysis in Kenneth Waltz’s Neorealism. In his The State, And War, Waltz argued for the "Levels of Analysis" and convinced the third level analyses a state’s legitimacy and goals via the international system’s responses and interactions. This paper examined the relationship between China’s standing in the eyes of the world and the acceptance of AIIB as a legitimate development institution.